Effective team leadership for engineers - Wellington, Pat; Foster, Niall (IET management of technology series, 2009)
Packed with practical information, advice and case studies, this book shows engineering team leaders how to get up to speed rapidly and efficiently, providing many useful and practical examples of real-life scenarios.